Carbon granule / zirconium silicate / zirconium oxide aerogel paper composite material as well as preparation method and application thereof

By using carbon particles/zirconium silicate/zirconium oxide aerogel paper composite in high-temperature insulation materials, the infrared absorption and scattering ability of carbon particles is used to solve the problem of the degradation of thermal insulation performance caused by infrared transparency of existing high-temperature insulation materials, the efficient radiant heat shielding effect is achieved and the low density and flexibility of the material are maintained.

CN119877316APending Publication Date: 2025-04-25CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411933322.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing high-temperature thermal insulation materials have deteriorated due to infrared transparency at high temperatures, and infrared light-shielding materials or a shielding layer structure are required to improve performance.

Method used

Using carbon particles/zirconium silicate/zirconium oxide aerogel paper composite material, zirconium oxide nanofiber aerogel paper is prepared by electrospinning, and a semi-reactive zirconium silicate precursor sol is loaded on its surface, and a composite material coated with carbon particles is prepared by synchronous calcination.

Benefits of technology

The composite material has an infrared absorption rate of more than 90% from 500 to 2000 nm, which effectively enhances the radiation heat shielding effect, and avoids the increase in density and thermal conductivity, maintains the low density and good flexibility of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877316A_ABST
    Figure CN119877316A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon granule / zirconium silicate / zirconium oxide aerogel paper composite material as well as a preparation method and application thereof. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, the zirconium oxide aerogel paper is composed of zirconium oxide nanofibers with the diameter of 100-400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with the particle size of 30-100 nm, and the thickness of the coating layer is 50-200 [mu] m. The invention aims to provide a carbon granule / zirconium silicate / zirconium oxide aerogel paper composite material, which can enhance the radiation heat shielding effect and avoid the increase of density and heat conductivity coefficient at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermal insulation materials, and specifically relates to a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material and a preparation method and application thereof. Background Art

[0002] High temperature / ultra-high temperature insulation is of great value in industrial production. On the one hand, it can reduce the heat loss of equipment such as high temperature kilns, and on the other hand, it can protect related equipment and personnel from damage in high temperature environments. At high temperatures, radiation heat transfer dominates the heat transfer process, and a large amount of heat will be transferred in the form of infrared rays. However, traditional insulation materials such as glass fiber, ceramic fiber, aerogel and other insulation materials usually have infrared transparency, resulting in a decrease in their high temperature insulation performance. Therefore, it is necessary to add infrared shading materials or structures to various insulation structures to meet the performance requirements of high temperature insulation. Among them, the means of adding infrared shading agents to the materials is mainly to add well-dispersed shading agent granular materials to the insulation materials, and use the scattering and absorption process of infrared rays by the shading agent particles to inhibit high temperature radiation heat transfer. Another way is to set a multi-layer shielding layer structure with the ability to absorb or reflect infrared rays in the middle of the insulation material, and form a multi-layer insulation material by alternating the two, thereby effectively reducing the impact of radiation heat transfer. Summary of the invention

[0003] In view of this, the main purpose of the present invention is to provide a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material and its preparation method and application. The problem to be solved is how to provide a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material that can enhance the radiation heat shielding effect while avoiding the increase of density and thermal conductivity.

[0004] The purpose of the present invention and the technical problem solved are achieved by adopting the following technical scheme. The present invention proposes a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconia aerogel paper, the zirconia aerogel paper is composed of zirconia nanofibers with a diameter of 100 to 400 nm, the surface of the zirconia aerogel paper is loaded with a coating layer of zirconium silicate, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 50 to 200 μm.

[0005] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0006] Preferably, the aforementioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material has an infrared absorption rate of more than 90% at 500 to 2000 nm.

[0007] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. A method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material proposed in the present invention comprises the following steps:

[0008] 1) Preparing zirconia nanofiber aerogel paper precursor by electrospinning;

[0009] 2) preparing a semi-reacted zirconium silicate precursor sol;

[0010] 3) preparing a zirconium oxide aerogel paper precursor loaded with a half-reacted zirconium silicate precursor;

[0011] 4) calcining the zirconium oxide nanofiber aerogel paper precursor loaded with the semi-reacted zirconium silicate precursor under the protection of an inert gas, and then cooling to room temperature to obtain the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material.

[0012] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0013] Preferably, in the method for preparing the aforementioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 1), the zirconium oxide precursor spinning solution used for electrospinning is prepared by the following steps:

[0014] The zirconium source is stirred and dissolved in a solvent, a phase stabilizer is added, stirred and dissolved, and then a spinning aid is added, stirred and dissolved to obtain the zirconium oxide precursor spinning solution.

[0015] Preferably, in the preparation method of the aforementioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 1), the mass ratio of the zirconium source, solvent, phase stabilizer and spinning aid is 1:0.3~0.6:0.03~0.05:0.05~0.08; the solvent is anhydrous ethanol or deionized water; the phase stabilizer is yttrium nitrate or yttrium chloride; and the spinning aid is polyvinyl pyrrolidone or polyethylene oxide.

[0016] Preferably, in the preparation method of the aforementioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 1), the operating parameters of the electrospinning are set as follows: the spinning voltage is 20-25 kV, the receiving distance is 18 cm, and the propulsion speed is 1.5 mL / h.

[0017] Preferably, in the aforementioned method for preparing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 2), the preparation of the semi-reacted zirconium silicate precursor sol comprises the following steps:

[0018] 21) dissolving the mineralizer in the organosilicon source to obtain an organosilicon source solution;

[0019] 22) dissolving inorganic zirconium in ethanol to obtain an inorganic zirconium solution;

[0020] 23) adding the organic silicon source solution obtained in step 21) to the inorganic zirconium source solution obtained in step 22), stirring for 1 to 3 hours to mix them evenly, and obtaining a mixed solution;

[0021] 24) The mixed solution obtained in step 23) is reacted at 110-120° C. for 10-12 hours, then cooled to 90-100° C. and continued to react for 10-12 hours, then cooled to room temperature to obtain a semi-reacted zirconium silicate precursor sol, which is allowed to stand for 12-24 hours for use.

[0022] Preferably, in the preparation method of the aforementioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 21), the molar ratio of the mineralizer to the organosilicon source is 0.3-0.4:1; the mineralizer is selected from one of lithium fluoride, sodium fluoride and calcium fluoride; and the organosilicon source is selected from one of tetraethyl orthosilicate, methyl orthosilicate, methyltriethoxysilane and dimethyldiethoxysilane.

[0023] Preferably, in the method for preparing the aforementioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 22), the concentration of the inorganic zirconium raw solution is 0.7-1.5 mol / L; in step 23), the silicon-zirconium molar ratio is 1.1-1.2:1.

[0024] Preferably, in the method for preparing the aforementioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 3), the preparation of the zirconium oxide aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor comprises the following steps:

[0025] The zirconia aerogel paper precursor is placed in a hot surface environment of 60 to 80°C, and a semi-reacted zirconium silicate precursor sol is sprayed on the surface of the zirconia aerogel paper precursor to be dried by heat to form a film spontaneously; the zirconia aerogel paper precursor is then further dried to obtain a zirconia nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor.

[0026] Preferably, in the method for preparing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 3), the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 to 60 mg / cm 2 The drying temperature is 60-90°C and the drying time is 0.5-2h.

[0027] Preferably, in the aforementioned method for preparing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, in step 4), the inert gas is nitrogen or argon.

[0028] Preferably, in the preparation method of the aforementioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, step 4) specifically comprises: placing the zirconium oxide nanofiber aerogel paper loaded with a semi-reacted zirconium silicate precursor in an inert gas atmosphere, first heating from room temperature to 450-500°C at a rate of 0.5-1°C / min, and keeping warm for 30-40 minutes; then heating to 850-900°C at a heating rate of 1-1.5°C / min, keeping warm for 2-3 hours, and then cooling to room temperature.

[0029] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a thermal radiation shielding layer, which adopts a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material; the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material includes zirconia aerogel paper, the zirconia aerogel paper is composed of zirconia nanofibers with a diameter of 100 to 400 nm, the zirconia aerogel paper is composed of zirconia nanofibers with a diameter of 100 to 400 nm, the surface of the zirconia aerogel paper is loaded with a coating layer of zirconium silicate, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 50 to 200 μm.

[0030] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a multi-layer thermal insulation material, which includes a thermal radiation shielding layer, and the thermal radiation shielding layer adopts a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material; the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material includes zirconia aerogel paper, and the zirconia aerogel paper is composed of zirconia nanofibers with a diameter of 100 to 400 nm, and the surface of the zirconia aerogel paper is loaded with a coating layer of zirconium silicate, and the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 50 to 200 μm.

[0031] By means of the above technical solution, the present invention provides a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material and a preparation method and application thereof, which have at least the following advantages:

[0032] The present invention uses zirconium oxide aerogel paper as a substrate, and a composite material with a zirconium silicate coating layer coated with carbon particles on the surface. The carbon particles themselves absorb and scatter infrared rays, so that the composite material can be used as an efficient thermal radiation shielding layer material, so that it can be combined with other thermal insulation materials to form a multi-layer thermal insulation material to enhance its ability to block radiant heat at high temperatures. At the same time, because the carbon particles coated with zirconium silicate can effectively isolate oxygen and enhance its antioxidant ability, it can be used in high temperature and oxygen-containing environments. In addition, the zirconium oxide aerogel paper is used as a substrate, which provides strength and flexibility while reducing the density of the shielding layer material. And the zirconium oxide nanoaerogel paper is composed of zirconium oxide nanofibers, which itself has a low solid-phase thermal conductivity, so that the shielding layer can not only reduce radiation heat transfer, but also take into account the thermal insulation effect. In the scenario where other types of thermal insulation materials are composited to form a multi-layer thermal insulation material, while enhancing the radiation heat shielding effect, it avoids the increase of density and thermal conductivity.

[0033] The present invention first prepares a zirconium oxide aerogel paper precursor by electrostatic spinning, and then uses ultrasonic spraying to load a semi-reacted zirconium silicate precursor sol thereon. Then, by means of synchronous calcination, the zirconium oxide nanofiber aerogel paper precursor is converted into a zirconium oxide aerogel paper substrate, and the semi-hydrolyzed zirconium silicate precursor loaded thereon is simultaneously converted into a zirconium silicate layer coated with carbon particles, so as to realize the synchronous preparation of carbon particles / zirconium silicate / zirconium oxide aerogel paper composite materials. The method utilizes in-situ carbonization of organic components in the semi-reacted zirconium silicate precursor, and carbon particles are embedded inside while forming a zirconium silicate layer. And its radiation shielding performance also mainly depends on the carbon particles coated inside the zirconium silicate layer, and the high absorption and scattering ability of the carbon particles to infrared rays enables it to play a radiation shielding function under high temperature and oxygen conditions. In addition, the zirconium silicate layer loaded on the surface of the zirconium oxide does not affect the flexibility of the obtained zirconium oxide aerogel paper, and is convenient for forming a multi-layer insulation structure with other insulation materials to play a radiation heat shielding function, avoiding the requirement that conventional sunscreen particles need to be directly dispersed inside the insulation material. In addition, zirconia aerogel paper is mainly composed of zirconia nanofibers, which have lower thermal conductivity and density, avoiding the influence of conventional metal shielding layers on the density and thermal conductivity of insulation materials.

[0034] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material of the present invention has an infrared absorption rate of more than 90% at 500-2000nm; the 0.12-0.13g / cm 3 When the hot surface temperature is 900℃, the cold surface temperature is 339℃-352℃; when the hot surface temperature is 1000℃, the cold surface temperature is 359℃-371℃.

[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention is a flow chart of the preparation of carbon particle / zirconium silicate / zirconium oxide aerogel paper composite materials according to some embodiments of the present invention;

[0037] Figure 2 This is a SEM image of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 1 of the present invention;

[0038] Figure 3 This is a photo of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material and its preparation method and application according to the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0040] The following materials or reagents, unless otherwise specified, were commercially available.

[0041] Some embodiments of the present invention provide a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material includes zirconia aerogel paper, the zirconia aerogel paper is composed of zirconia nanofibers with a diameter of 100 to 400 nm, the surface of the zirconia aerogel paper is loaded with a coating layer of zirconium silicate, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 50 to 200 μm; if the thickness is less than 50 μm, the thickness is too thin and the thermal radiation shielding effect is poor, and if the thickness is greater than 200 μm, the thickness is too thick and affects the flexibility of the aerogel paper. According to tests, the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is more than 90%.

[0042] The purpose of designing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material is to form an infrared radiation shielding layer structure, in which the infrared shielding function is performed by the carbon particles generated in situ in the zirconium silicate layer, mainly by virtue of the carbon material's own strong absorption and scattering function of infrared rays. However, carbon materials are prone to rapid oxidation loss in high-temperature (greater than 450°C) aerobic environments and cannot be directly used in high-temperature thermal insulation materials. The continuous and dense zirconium silicate ceramic layer has good high-temperature stability and can block the contact between the oxygen in the environment and the internal carbon particles, thereby ensuring the stable existence of the internal carbon particles at high temperatures and effectively playing the role of shielding infrared radiation at high temperatures.

[0043] Zirconia fiber aerogel paper is composed of zirconium oxide nanofibers, which have good high temperature stability and low solid-phase thermal conductivity, and can be conveniently used as a flexible paper-like substrate. After the semi-reacted zirconium silicate precursor is loaded on its surface and the zirconium silicate layer is loaded on the surface after heat treatment, it can still maintain its own flexibility, which is convenient for replacing traditional metal foil as a shielding layer, and can effectively make up for the shortcomings of high thermal conductivity and high density of traditional metal foil shielding layers.

[0044] The carbon particles in the zirconium silicate layer are introduced in situ. When synthesizing the zirconium silicate precursor, the zirconium silicate precursor is kept in a semi-reacted state, so that there are enough unreacted organic groups left inside and outside the colloidal particles in the zirconium silicate sol. The remaining organic groups can be used as a carbon source for in-situ conversion of carbon particles, and evenly dispersed carbon particles are formed in situ during the zirconium silicate sintering process. Therefore, well-dispersed carbon particles can be obtained without the need to add additional carbon particles or other carbon sources, eliminating the need for additional doping and dispersion processes.

[0045] like Figure 1 As shown, some embodiments of the present invention also provide a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0046] S 1, prepare zirconium oxide precursor spinning solution

[0047] S11 dissolves the zirconium source in a solvent and stirs to dissolve. Since acetate does not introduce other heteroatoms and is easily removed by heating and volatilization, zirconium acetate is selected as the zirconium source instead of other zirconium sources. The solvent can be water or anhydrous ethanol, which has relatively good solubility for zirconium acetate and the phase stabilizer.

[0048] S12: adding a phase stabilizer to the above solution and stirring to dissolve. The phase stabilizer is generally an inorganic salt containing yttrium. Considering the solubility, yttrium nitrate or yttrium chloride with good solubility should be used; the presence of the phase stabilizer can ensure the stability of zirconium oxide at high temperatures.

[0049] S13 adds a spinning aid to the above-mentioned solution. The spinning aid can be one of the polymer materials such as polyvinyl pyrrolidone (PVP), polyethylene oxide (PEO), carboxymethyl cellulose, etc. Considering the compatibility and spinnability, polyvinyl pyrrolidone (PVP) or polyethylene oxide (PEO) is preferred. The mass ratio of the above-mentioned zirconium source, solvent, phase stabilizer, and spinning aid is 1: 0.3-0.6: 0.03-0.05: 0.05-0.08. Too low or too high a solvent content, or too high or too low a spinning aid content, will cause the viscosity of the spinning solution to be too high or too low, resulting in discontinuous and unformed spinning, or uneven diameter of the obtained nanofibers. Too high or too low a phase stabilizer content will result in the inability to stabilize zirconium oxide.

[0050] S14: Stir the above solution at room temperature for 0.5 to 1.5 hours to obtain a spinning solution. If the stirring time is less than 0.5 hours, the stirring time is too short and the mixing is uneven, resulting in an uneven solution, which affects the spinning effect. If the stirring time is greater than 1.5 hours, the stirring time is too long, which may cause excessive evaporation of the solvent and result in excessively high viscosity of the solution.

[0051] S2, Preparation of zirconia nanofiber aerogel paper precursor by electrospinning

[0052] S21, using electrostatic spinning equipment for spinning, the spinning voltage is 20-25kV, the receiving distance is 17-19cm, preferably 18cm, and the propulsion speed is 1.3-1.7ml / l, preferably 1.5mL / h. If the spinning voltage is too high (greater than 25kV) or the spinning distance is too small (for example, less than 17cm), the spinning fiber tension will be too large and the spinning will be discontinuous. If the spinning voltage is too low (less than 20kV) or the spinning distance is too large (for example, more than 19cm), the tension will be insufficient, and the fiber diameter will be too large or uneven. When it is less than 1.3ml / L, the propulsion speed is too small, the solution is insufficient, and the spinning is discontinuous. When it is greater than 1.7ml / L, the propulsion speed is too large, affecting the spinning quality.

[0053] S22, when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel is 0.2-0.4 mm, the spinning is stopped, and the obtained zirconia aerogel paper precursor is taken out. If the thickness is less than 0.2 mm, the spun paper precursor is too thin, the strength is insufficient, and it is easy to tear. If the thickness is greater than 0.4 mm, the spinning thickness is too thick, which will cause the composite paper obtained later to be too thick, affecting its flexibility.

[0054] S23, putting the obtained zirconia aerogel paper precursor into a blast oven, drying it at 90-120°C, preferably 100°C for more than 1.5 hours for later use. When the temperature is too low (e.g., less than 90°C), the solvent is not completely dried. When the temperature is too high (e.g., greater than 120°C), the drying speed is too fast, which may cause the fiber paper to crack and affect the quality of the fiber paper.

[0055] S3, preparation of semi-reacted zirconium silicate sol

[0056] S31 dissolves the mineralizer in the organosilicon source to obtain an organosilicon source solution; the molar ratio of the mineralizer to the organosilicon source is 0.3 to 0.4:1. The mineralizer may be a fluoride salt such as lithium fluoride, sodium fluoride or calcium fluoride, preferably lithium fluoride, which is optimal for improving the crystallinity and phase purity of calcium silicate. The organosilicon source may be tetraethyl orthosilicate (TEOS), methyl orthosilicate, methyltriethoxysilane or dimethyldiethoxysilane, etc. Considering its dispersibility in ethanol, and the compatibility and safety of the byproducts and ethanol after forming the sol, tetraethyl orthosilicate is preferred. If the molar ratio of the mineralizer to the organosilicon source is less than 0.3:1, the content of the mineralizer is too low, and the synthesis temperature of zirconium silicate cannot be effectively reduced, resulting in low crystallinity of zirconium silicate and a large amount of zirconium oxide. If the molar ratio of the mineralizer to the organic silicon source is greater than 0.4:1, the lithium fluoride content is too high, too much SiF4 gas is generated during the reaction, excessive silicon is lost, and the zirconium silicate content is reduced.

[0057] S32 dissolves the inorganic zirconium source in anhydrous ethanol to obtain an inorganic zirconium source solution; the solution concentration is 0.7-1.5 mol / L. Considering that zirconium chloride can react with ethanol to generate zirconium oxychloride intermediates and disperse in ethanol to form a solution, the inorganic zirconium source is zirconium chloride (ZrCl4); below 0.7 mol / L, the solvent content is too high, which easily leads to the zirconium silicate precursor being not dense enough after drying. Above 1.5 mol / L, the solution viscosity is too high, affecting the spraying effect, the film-forming property is too poor, and it is easy to crack.

[0058] S33: Add the organic silicon source solution to the inorganic zirconium source solution, stir for 1 to 3 hours, preferably 1 hour, to make it evenly mixed, wherein the silicon-zirconium molar ratio is 1.1 to 1.2:1, preferably 1.2:1; stir to make it evenly mixed, and completely react to convert it into a zirconium oxychloride intermediate. When the stirring time is less than 1 hour, the reaction is incomplete, and too long stirring time is likely to produce by-products that are not conducive to subsequent reactions; when the silicon-zirconium molar ratio is less than 1.1:1, the silicon element is insufficient, and an excessive zirconium oxide phase will be produced. When it is greater than 1.2:1, the silicon element is excessive, and an excessive silicon dioxide phase will be produced.

[0059] S34 Add the above mixed solution into a round-bottom flask, connect a cooling reflux device, and react at 110-120°C for 10-12h to complete the first stage reaction. If the reaction temperature is too low (lower than 110°C) or the reaction time is too short (less than 10h) in the first stage, the reaction will be too slow, resulting in insufficient sol particles produced in the early stage. If the reaction temperature is too high (greater than 120°C) or the reaction time is too long (greater than 12h), the early sol reaction will be too thorough, which is not conducive to the subsequent reaction process to produce enough residual organic groups as carbon sources; then cool to 90-100°C and continue to react for 10-12h to complete the second stage reaction, then cool to room temperature to obtain a semi-reacted zirconium silicate precursor sol, which is left to stand for 12-24h for use. If the reaction temperature in the second stage is too low (below 90°C) or the reaction time is too short (less than 10h), it is easy to cause insufficient reaction and too low content of zirconium silicate precursor sol; if the reaction temperature is too high (above 120°C) or the reaction time is too long (greater than 12h), the reaction will be too complete and insufficient organic groups will not be retained, that is, the semi-reaction state cannot be achieved. The sol can be stabilized by standing for 12-24h; if it is less than 12h, the time is too short and the semi-reaction sol system is unstable; if it is more than 24h, it may cause the sol to solidify.

[0060] S4, preparation of zirconia aerogel paper precursor loaded with semi-reacted zirconium silicate precursor

[0061] S41: Place the zirconia aerogel paper precursor on a heating plate and set the temperature of the heating plate to 60-80°C. If the temperature is too low (less than 60°C), the drying will be too slow after spraying, which may cause the solution to penetrate into the interior of the zirconia aerogel paper precursor. If the temperature is too high (greater than 80°C), the drying speed will be too fast, which will affect the film-forming effect and may cause the film layer to crack.

[0062] S42 uses an ultrasonic spray device to spray a semi-reacted zirconium silicate precursor sol on the surface of the zirconium oxide aerogel paper precursor, so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25-60 mg / cm 2 If less than 25mg / cm 2 If the spraying amount is too low, the carbon particle / zirconium silicate loading will be low, the coating layer will be discontinuous, and the thermal radiation shielding effect of the shielding layer will be affected. 2 If the spraying amount is too high, the composite paper will be densified as a whole and its flexibility will be reduced. Dispersing the precursor sol into micron droplets by ultrasonic atomization can make it form a film more uniformly on the porous surface of the zirconia aerogel paper precursor.

[0063] After S43 is finished spraying, the above-mentioned zirconium oxide aerogel paper precursor is placed in a blast oven, the temperature is set to 60-90°C, preferably 80°C, and dried for 0.5-2h, preferably 0.5h, to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor. If the drying temperature is too low (for example, below 60°C), the drying time will be too long. If the drying temperature is too high (for example, above 120°C), the drying speed will be too fast, which may cause cracking of the sprayed film layer. If the initial drying time is less than 0.5h, it is easy to cause incomplete initial drying, too high solvent content, and insufficient density of the film layers. If the drying time is too long, it is easy to cause too many cracks in the film layer;

[0064] S5, Synchronous calcination to prepare carbon particle / zirconium silicate / zirconium oxide aerogel paper composites

[0065] The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor is placed in an atmosphere furnace, and an inert gas (nitrogen or argon) is used as a protective gas. First, the temperature is raised from room temperature to 450-500°C at a rate of 0.5-1°C / min. If the rate is greater than 1°C / min, the temperature rises too fast, resulting in a small amount of residual solvent or volatile organic gas volatilizing too fast, which easily leads to cracking of the film layer. If the rate is less than 0.5°C / min, the temperature rise is too slow, affecting the overall preparation efficiency; choose to keep warm between 450-550°C, at which time zirconium silicate does not begin to be generated, and excess organic solvents and gases can be eliminated to stabilize the system; keep warm for 30-40 minutes, preferably 30 minutes; keep warm for 30-40 minutes to make the furnace temperature uniform, which is conducive to the stability of the next heating rate. If it is less than 30 minutes, the time is too short and the furnace temperature is unstable. If it is greater than 40 minutes, the time is too long, which reduces the synthesis efficiency. Then, the temperature is raised to 850-900℃ at a heating rate of 1-1.5℃ / min, kept at this temperature for 2-3h, and then cooled to room temperature; if the heating rate is less than 1℃ / min, the heating rate is too slow, which will cause grain coarsening and affect the uniformity of the film layer. If the heating rate is greater than 1.5℃ / min, the heating rate is too fast, which will cause too fast reaction and easy cracking of the film layer. When the temperature is less than 850℃, the temperature is too low, resulting in insufficient crystallinity of zirconium silicate. When the temperature is greater than 900℃, the temperature is too high, which will cause excessive coarsening of the grains. When the holding time is less than 2h, the time is too short, resulting in insufficient crystallinity of zirconium silicate; when the holding time is greater than 3h, the time is too long, resulting in excessive coarsening of the grains.

[0066] Some embodiments of the present invention also provide a heat radiation shielding layer, which can be made of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. According to tests, the infrared absorption rate of the heat radiation shielding layer at 500-2000nm is above 90%.

[0067] Some embodiments of the present invention further provide a multilayer thermal insulation material, the multilayer thermal insulation material comprising a thermal radiation shielding layer, the thermal radiation shielding layer can be made of the above-mentioned carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. According to tests, the thermal insulation material has a thermal conductivity of 0.12-0.13 g / cm 3 When the hot surface temperature is 900℃, the cold surface temperature is 339℃-352℃; when the hot surface temperature is 1000℃, the cold surface temperature is 359℃-371℃.

[0068] In the above technical scheme, the present invention uses the residual organic groups in the semi-reacted zirconium silicate precursor sol as a carbon source for carbon particles, and converts them into a zirconium silicate layer containing a large number of carbon particles, so that it has a shielding effect on thermal radiation, and the zirconium silicate layer can protect the carbon particles from being oxidized and decomposed at high temperatures. The zirconium oxide aerogel paper precursor as a substrate is composed of nanofibers produced by electrospinning. After loading the semi-reacted zirconium silicate sol precursor, it is converted into a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material through synchronous calcination, maintaining the overall low density and good flexibility of the material, and can be conveniently used as a thermal radiation shielding layer to form a multi-layer thermal insulation material with various types of thermal insulation materials.

[0069] The specific implementation methods of the present invention are further described in detail below in conjunction with the embodiments, but it should not be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0070] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0071] Example 1

[0072] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0073] (1) Mix 7.8 ml of zirconium acetate, 0.3 g of yttrium chloride and 6 ml of anhydrous ethanol to obtain a zirconium acetate solution;

[0074] (2) adding 0.5 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stirring at room temperature for 1 h to obtain a spinning solution;

[0075] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0076] (4) stirring and mixing 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0077] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix the mixture evenly, to obtain a second mixed solution;

[0078] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0079] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0080] (8) using an ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0081] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0082] (10) The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor obtained in step (9) is placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) is used as a protective gas. The temperature is first increased from room temperature to 500° C. at a rate of 1° C. / min, and kept at this temperature for 30 min; then the temperature is increased to 900° C. at a rate of 1.5° C. / min, and kept at this temperature for 2 h, and then the temperature is cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 80 to 150 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0083] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 1 is used as a heat radiation shielding layer and combined with aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: four layers of the composite material described in Example 1 with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are arranged between five layers of aluminum silicate needle-punched felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, respectively, to form a multilayer thermal insulation material together, and the density is 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 900°C, the cold surface temperature was 352°C.

[0084] from Figure 2 It can be observed that the zirconium silicate coating layer of this example is attached to the surface of the zirconium oxide aerogel paper. Figure 3 It can be observed that the uniformly dispersed carbon particles generated in situ in the zirconium silicate coating layer make the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in this example appear obviously black.

[0085] Example 2

[0086] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0087] (1) Mix 13.2 ml of zirconium acetate, 0.75 g of yttrium chloride and 10 ml of deionized water to obtain a zirconium acetate solution;

[0088] (2) Add 1.2 g of polyethylene oxide (PEO) to the zirconium acetate solution obtained in step (1), and stir at room temperature for 1 h to obtain a spinning solution.

[0089] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0090] (4) stirring and mixing 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0091] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix well, to obtain a second mixed solution;

[0092] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a conventional cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0093] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0094] (8) using an ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor, so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0095] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0096] (10) The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor obtained in step (9) is placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) is used as a protective gas. The temperature is first increased from room temperature to 500° C. at a rate of 1° C. / min, and kept at this temperature for 30 min; then the temperature is increased to 900° C. at a rate of 1.5° C. / min, and kept at this temperature for 2 h, and then the temperature is cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 80 to 150 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0097] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 2 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: between five layers of aluminum silicate needle-punched felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, four layers of composite radiation heat shielding layer materials of Example 2 with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are respectively arranged, together forming a multilayer thermal insulation material, the density of which is 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 900°C, the cold surface temperature was 347°C.

[0098] Example 3

[0099] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0100] (1) Mix 13.2 ml of zirconium acetate, 0.75 g of yttrium chloride and 10 ml of deionized water to obtain a zirconium acetate solution.

[0101] (2) Add 1.2 g of polyethylene oxide (PEO) to the zirconium acetate solution obtained in step (1), and stir at room temperature for 1 h to obtain a spinning solution.

[0102] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0103] (4) stirring and mixing 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0104] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix well, and obtaining a mixed solution;

[0105] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0106] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0107] (8) using an ultrasonic spray device to spray a semi-reacted zirconium silicate precursor sol onto the surface of the zirconium oxide aerogel paper precursor, so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0108] (9) After spraying, the zirconium oxide aerogel paper precursor is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0109] (10) The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor was placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) was used as a protective gas. The temperature was first increased from room temperature to 500°C at a rate of 1°C / min and kept at this temperature for 30 minutes; then the temperature was increased to 900°C at a rate of 1.5°C / min, kept at this temperature for 2 hours, and then cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite radiation heat shielding material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 80 to 150 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0110] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 3 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: between five layers of aluminum silicate needle-punched felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, four layers of composite radiation heat shielding layer materials of Example 3 with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are respectively arranged, together forming a multilayer thermal insulation material, the density of which is 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 900°C, the cold surface temperature was 341°C.

[0111] Example 4

[0112] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0113] (1) Mix 8 ml of zirconium acetate, 0.41 g of yttrium nitrate and 5 ml of anhydrous ethanol to obtain a zirconium acetate solution.

[0114] (2) Add 0.58 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stir at room temperature for 1 h to obtain a spinning solution.

[0115] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0116] (4) stirring and mixing 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0117] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix well, and obtaining a mixed solution;

[0118] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0119] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0120] (8) using an ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0121] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0122] (10) The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor obtained in step (9) is placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) is used as a protective gas. The temperature is first increased from room temperature to 500° C. at a rate of 1° C. / min, and kept at this temperature for 30 min; then the temperature is increased to 900° C. at a rate of 1.5° C. / min, and kept at this temperature for 2 h, and then the temperature is cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 80 to 150 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0123] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 4 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: four layers of composite radiation heat shielding layer materials of Example 4 with dimensions of 50 mm long*50 mm wide and 0.25 mm thick are arranged between five layers of aluminum silicate needle-punched felt with dimensions of 50 mm long*50 mm wide and 2 mm thick, to form a multilayer thermal insulation material with a density of 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 900°C, the cold surface temperature was 347°C.

[0124] Example 5

[0125] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0126] (1) Mix 7.8 ml of zirconium acetate, 0.3 g of yttrium chloride and 6 ml of anhydrous ethanol to obtain a zirconium acetate solution;

[0127] (2) adding 0.5 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stirring at room temperature for 1 h to obtain a spinning solution;

[0128] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.35 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0129] (4) 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) were stirred and mixed to obtain a first mixed solution;

[0130] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix well, and obtaining a mixed solution;

[0131] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0132] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0133] (8) using an ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0134] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0135] (10) The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor obtained in step (9) is placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) is used as a protective gas. The temperature is first increased from room temperature to 500° C. at a rate of 1° C. / min, and kept at this temperature for 30 min; then the temperature is increased to 900° C. at a rate of 1.5° C. / min, and kept at this temperature for 2 h, and then the temperature is cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 80 to 150 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0136] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 5 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: four layers of the composite radiation heat shielding layer material of Example 5 with a size of 50 mm long * 50 mm wide and a thickness of 0.35 mm are arranged between five layers of aluminum silicate needle felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, respectively, to form a multilayer thermal insulation material with a density of 0.12 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 900°C, the cold surface temperature was 339°C.

[0137] Example 6

[0138] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0139] (1) Mix 7.8 ml of zirconium acetate, 0.3 g of yttrium chloride and 6 ml of anhydrous ethanol to obtain a zirconium acetate solution;

[0140] (2) adding 0.5 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stirring at room temperature for 1 h to obtain a spinning solution;

[0141] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0142] (4) 0.65 g of lithium fluoride (LiF) and 15.9 ml of tetraethyl orthosilicate (TEOS) were stirred and mixed to obtain a first mixed solution.

[0143] (5) Add 75 ml of 0.8 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4) and stir for 1 h to mix well.

[0144] (6) Add the second mixed solution obtained in step (5) into a round-bottom flask, connect a cooling reflux device, react at 110° C. for 12 h, then cool to 100° C. and continue to react for 12 h, then cool to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and let it stand for 24 h for use.

[0145] (7) Place the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and set the heating plate temperature to 60°C.

[0146] (8) using an ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0147] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0148] (10) The zirconia nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor was placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) was used as a protective gas. The temperature was first increased from room temperature to 500°C at a rate of 1°C / min and kept at this temperature for 30 minutes; then the temperature was increased to 900°C at a rate of 1.5°C / min, kept at this temperature for 2 hours, and then cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 60 to 120 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0149] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 6 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: four layers of composite radiation heat shielding layer materials of Example 6 with dimensions of 50 mm long*50 mm wide and 0.25 mm thick are arranged between five layers of aluminum silicate needle-punched felt with dimensions of 50 mm long*50 mm wide and 2 mm thick, to form a multilayer thermal insulation material with a density of 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 1000°C, the cold surface temperature was 362°C.

[0150] Example 7

[0151] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0152] (1) Mix 7.8 ml of zirconium acetate, 0.3 g of yttrium chloride and 6 ml of anhydrous ethanol to obtain a zirconium acetate solution;

[0153] (2) adding 0.5 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stirring at room temperature for 1 h to obtain a spinning solution;

[0154] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0155] (4) stirring and mixing 0.8 g of lithium fluoride (LiF) and 18 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0156] (5) adding 54.5 ml of 1.5 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix well, and obtaining a mixed solution;

[0157] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0158] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0159] (8) using an ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0160] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0161] (10) The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor obtained in step (9) is placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) is used as a protective gas. The temperature is first increased from room temperature to 500° C. at a rate of 1° C. / min, and kept at this temperature for 30 min; then the temperature is increased to 900° C. at a rate of 1.5° C. / min, and kept at this temperature for 2 h, and then the temperature is cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 100 to 200 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0162] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 7 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: between five layers of aluminum silicate needle-punched felt with a size of 50 mm long*50 mm wide and a thickness of 2 mm, four layers of composite radiation heat shielding layer materials of Example 7 with a size of 50 mm long*50 mm wide and a thickness of 0.25 mm are arranged respectively, together forming a multilayer thermal insulation material with a density of 0.12 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 1000°C, the cold surface temperature was 371°C.

[0163] Example 8

[0164] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0165] (1) Mix 7.8 ml of zirconium acetate, 0.3 g of yttrium chloride and 6 ml of anhydrous ethanol to obtain a zirconium acetate solution;

[0166] (2) adding 0.5 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stirring at room temperature for 1 h to obtain a spinning solution;

[0167] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0168] (4) stirring and mixing 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0169] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix well, and obtaining a mixed solution;

[0170] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a cooling reflux device, reacting at 120° C. for 10 h, then cooling to 90° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 18 h for later use;

[0171] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0172] (8) using an ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0173] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0174] (10) The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor obtained in step (9) is placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) is used as a protective gas. The temperature is first increased from room temperature to 500° C. at a rate of 1° C. / min, and kept at this temperature for 30 min; then the temperature is increased to 900° C. at a rate of 1.5° C. / min, and kept at this temperature for 2 h, and then the temperature is cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 80 to 150 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0175] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 8 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: between five layers of aluminum silicate needle-punched felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, four layers of composite radiation heat shielding layer materials of Example 8 with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are respectively arranged, together forming a multilayer thermal insulation material, the density of which is 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 1000°C, the cold surface temperature was 359°C.

[0176] Example 9

[0177] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0178] (1) Mix 7.8 ml of zirconium acetate, 0.3 g of yttrium chloride and 6 ml of anhydrous ethanol to obtain a zirconium acetate solution;

[0179] (2) adding 0.5 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stirring at room temperature for 1 h to obtain a spinning solution;

[0180] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0181] (4) stirring and mixing 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0182] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix well, and obtaining a mixed solution;

[0183] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0184] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 65° C.;

[0185] (8) using an ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 35 mg / cm 2 ;

[0186] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0187] (10) The zirconia nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor was placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) was used as a protective gas. The temperature was first increased from room temperature to 500°C at a rate of 1°C / min and kept at this temperature for 30 minutes; then the temperature was increased to 900°C at a rate of 1.5°C / min, kept at this temperature for 2 hours, and then cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 120 to 200 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0188] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 9 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: four layers of the composite radiation heat shielding layer material of Example 9 with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are arranged between five layers of aluminum silicate needle felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, respectively, to form a multilayer thermal insulation material with a density of 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 1000°C, the cold surface temperature was 364°C.

[0189] Example 10

[0190] This embodiment provides a method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, comprising the following steps:

[0191] (1) Mix 7.8 ml of zirconium acetate, 0.3 g of yttrium chloride and 6 ml of anhydrous ethanol to obtain a zirconium acetate solution;

[0192] (2) adding 0.5 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stirring at room temperature for 1 h to obtain a spinning solution;

[0193] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0194] (4) stirring and mixing 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0195] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix well, and obtaining a mixed solution;

[0196] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a conventional cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0197] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0198] (8) using a conventional ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0199] (9) After spraying, the zirconium oxide aerogel precursor paper obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0200] (10) The zirconia nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor was placed in an atmosphere furnace, and pure argon (purity of 99.99%) was used as a protective gas. The temperature was first increased from room temperature to 450°C at a rate of 0.8°C / min and kept at this temperature for 40 min; then the temperature was increased to 850°C at a rate of 1.3°C / min, kept at this temperature for 2.5 h, and then cooled to room temperature to obtain a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, which is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 80 to 150 μm; the infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500 to 2000 nm is above 90%.

[0201] The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Example 10 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multilayer thermal insulation material, the structure of which is as follows: four layers of the composite radiation heat shielding layer material of Example 10 with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are arranged between five layers of aluminum silicate needle felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, respectively, to form a multilayer thermal insulation material with a density of 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 1000°C, the cold surface temperature was 366°C.

[0202] Comparative Example 1

[0203] Compared with Example 1, after completing steps (1) to (3), the material of this comparative example is directly transferred to an atmosphere furnace for heat treatment to obtain the material of Comparative Example 1, which specifically includes the following steps:

[0204] (1) Mix 7.8 ml of zirconium acetate, 0.3 g of yttrium chloride and 6 ml of anhydrous ethanol to obtain a zirconium acetate solution;

[0205] (2) adding 0.5 g of polyvinyl pyrrolidone (PVP) to the zirconium acetate solution obtained in step (1), and stirring at room temperature for 1 h to obtain a spinning solution;

[0206] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0207] (4) The zirconium oxide aerogel paper precursor was placed in an atmosphere furnace, and pure nitrogen (purity of 99.99%) was used as a protective gas. The temperature was first increased from room temperature to 500°C at a rate of 1°C / min, and kept at this temperature for 30 minutes; then the temperature was increased to 900°C at a rate of 1.5°C / min, and kept at this temperature for 2 hours, and then the temperature was cooled to room temperature to obtain the composite paper material of Comparative Example 1.

[0208] The composite paper material obtained in Comparative Example 1 is used as a heat radiation shielding layer and combined with aluminum silicate fiber felt to form a multi-layer thermal insulation material, the structure of which is as follows: four layers of the composite paper material of Comparative Example 1 with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are arranged between five layers of aluminum silicate needle felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, to form a multi-layer thermal insulation material with a density of 0.12 g / cm 3(Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 900°C, the cold surface temperature was 395°C.

[0209] Comparative Example 2

[0210] Compared with Example 2, after completing steps (1) to (9), the material of this comparative example is directly transferred to a gas muffle furnace and heat-treated in an air atmosphere to obtain the material of comparative example 2, which specifically includes the following steps:

[0211] (1) Mix 13.2 ml of zirconium acetate, 0.75 g of yttrium chloride and 10 ml of deionized water to obtain a zirconium acetate solution.

[0212] (2) Add 1.2 g of polyethylene oxide (PEO) to the zirconium acetate solution obtained in step (1), and stir at room temperature for 1 h to obtain a spinning solution.

[0213] (3) The spinning solution obtained in step (2) is injected into a syringe, loaded into an electrospinning device, and the electrospinning device is used for spinning, with a spinning voltage of 20 kV, a receiving distance of 18 cm, and a propulsion speed of 1.5 mL / h; when the thickness of the zirconia aerogel paper precursor obtained on the receiving barrel of the electrospinning machine is 0.25 mm, the spinning is stopped, and the zirconia aerogel paper precursor obtained is taken out, placed in a blast oven, and dried at 100° C. for 1.5 h for standby use;

[0214] (4) stirring and mixing 0.47 g of lithium fluoride (LiF) and 13.3 ml of tetraethyl orthosilicate (TEOS) to obtain a first mixed solution;

[0215] (5) adding 50 ml of 1 mol / L ZrCl4 ethanol solution to the first mixed solution obtained in step (4), stirring for 1 h to mix evenly, and obtaining a mixed solution;

[0216] (6) adding the second mixed solution obtained in step (5) into a round-bottom flask, connecting a cooling reflux device, reacting at 110° C. for 12 h, then cooling to 100° C. and continuing to react for 12 h, then cooling to room temperature to obtain a semi-reacted zirconium silicate precursor sol, and standing for 24 h for use;

[0217] (7) placing the zirconium oxide aerogel paper precursor obtained in step (3) on a heating plate and setting the temperature of the heating plate to 60° C.;

[0218] (8) using a conventional ultrasonic spray device to spray the semi-reacted zirconium silicate precursor sol obtained in step (6) onto the surface of the zirconium oxide aerogel paper precursor obtained in step (7), so that it is heated and dried to form a film spontaneously; wherein the spraying amount of the semi-reacted zirconium silicate precursor sol is 25 mg / cm 2 ;

[0219] (9) After spraying, the zirconium oxide aerogel paper precursor obtained in step (8) is placed in a blast oven, the temperature is set to 80° C., and dried for 0.5 h to obtain a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor;

[0220] (10) The zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor obtained in step (9) is placed in a muffle furnace. In an air atmosphere, the temperature is first increased from room temperature to 500° C. at a rate of 1° C. / min and kept at this temperature for 30 min; then the temperature is increased to 900° C. at a rate of 1.5° C. / min and kept at this temperature for 2 h, and then the temperature is cooled to room temperature to obtain the composite paper material of Comparative Example 2.

[0221] The composite paper material obtained in Comparative Example 2 is used as a heat radiation shielding layer and combined with the aluminum silicate fiber felt to form a multi-layer thermal insulation material, the structure of which is as follows: four layers of the composite paper material of Comparative Example 2 with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are arranged between five layers of aluminum silicate needle felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, to form a multi-layer thermal insulation material with a density of 0.13 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 900°C, the cold surface temperature was 402°C.

[0222] Comparative Example 3

[0223] This comparative example uses a stainless steel foil with a thickness of 0.25 mm as a heat radiation shielding layer and combines it with aluminum silicate fiber felt to form a multi-layer heat insulation material. Its structure is that four layers of stainless steel foil with a size of 50 mm long * 50 mm wide and a thickness of 0.25 mm are arranged between five layers of aluminum silicate needle felt with a size of 50 mm long * 50 mm wide and a thickness of 2 mm, and together constitute a multi-layer heat insulation material with a density of 0.35 g / cm 3 (Tested by weighing method). The thermal insulation performance was tested by using a flat plate thermal assessment device. When the hot surface temperature was 900°C, the cold surface temperature was 383°C.

[0224] The performance test data of the multilayer thermal insulation materials of Examples 1-10 and Comparative Examples 1-3 are summarized in Table 1.

[0225] Table 1

[0226]

[0227] From the data in Table 1, it can be seen that the multilayer thermal insulation material using the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material obtained in Examples 1 to 10 as a thermal radiation shielding layer has a lower back surface temperature, indicating that the shielding layer can reduce the transfer of radiant heat radiation and improve the thermal insulation capacity. The multilayer thermal insulation material of Examples 1 to 10 has a heat radiation shielding layer of 0.12-0.13 g / cm 3 When the hot surface temperature is 900℃, the cold surface temperature is 339℃-352℃; when the hot surface temperature is 1000℃, the cold surface temperature is 359℃-371℃.

[0228] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0229] The numerical range described in the present invention includes all the numerical values ​​within the range, and includes the range value formed by any two numerical values ​​within the range. Different numerical values ​​of the same indicator appearing in all embodiments of the present invention can be arbitrarily combined to form a range value.

[0230] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0231] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, characterized in that: The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material comprises zirconium oxide aerogel paper, wherein the zirconium oxide aerogel paper is composed of zirconium oxide nanofibers with a diameter of 100 to 400 nm, a zirconium silicate coating layer is loaded on the surface of the zirconium oxide aerogel paper, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the coating layer has a thickness of 50 to 200 μm.

2. The carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material according to claim 1, characterized in that: The infrared absorption rate of the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material at 500-2000nm is above 90%.

3. A method for preparing a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material, characterized in that: The following steps are involved: 1) Preparing zirconia nanofiber aerogel paper precursor by electrospinning; 2) preparing a semi-reacted zirconium silicate precursor sol; 3) preparing a zirconium oxide aerogel paper precursor loaded with a half-reacted zirconium silicate precursor; 4) calcining the zirconium oxide nanofiber aerogel paper precursor loaded with the semi-reacted zirconium silicate precursor under the protection of an inert gas, and then cooling to room temperature to obtain the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material.

4. The method for preparing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material according to claim 3, characterized in that: In step 1), the zirconium oxide precursor spinning solution used for electrospinning is prepared by the following steps: The zirconium source is stirred and dissolved in a solvent, a phase stabilizer is added, stirred and dissolved, and then a spinning aid is added, stirred and dissolved to obtain the zirconium oxide precursor spinning solution; The mass ratio of the zirconium source, solvent, phase stabilizer and spinning aid is 1:0.3-0.6:0.03-0.05:0.05-0.08; the solvent is anhydrous ethanol or deionized water; the phase stabilizer is yttrium nitrate or yttrium chloride; the spinning aid is polyvinyl pyrrolidone or polyethylene oxide; the operating parameters of the electrospinning are set as follows: the spinning voltage is 20-25 kV, the receiving distance is 17-19 cm, and the propulsion speed is 1.3-1.7 mL / h.

5. The method for preparing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material according to claim 3, characterized in that: In step 2), the preparation of the half-reacted zirconium silicate precursor sol comprises the following steps: 21) dissolving the mineralizer in the organosilicon source to obtain an organosilicon source solution; 22) dissolving inorganic zirconium in ethanol to obtain an inorganic zirconium solution; 23) adding the organic silicon source solution obtained in step 21) to the inorganic zirconium source solution obtained in step 22), stirring for 1 to 3 hours to mix them evenly, and obtaining a mixed solution; 24) The mixed solution obtained in step 23) is reacted at 110-120° C. for 10-12 hours, then cooled to 90-100° C. and continued to react for 10-12 hours, then cooled to room temperature to obtain a semi-reacted zirconium silicate precursor sol, which is allowed to stand for 12-24 hours for use.

6. The method for preparing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material according to claim 5, characterized in that: In step 21), the molar ratio of the mineralizer to the organosilicon source is 0.3 to 0.4:1; the mineralizer is selected from one of lithium fluoride, sodium fluoride and calcium fluoride; the organosilicon source is selected from one of ethyl orthosilicate, methyl orthosilicate, methyltriethoxysilane and dimethyldiethoxysilane; in step 22), the concentration of the inorganic zirconium original solution is 0.7 to 1.5 mol / L; in step 23), the molar ratio of silicon to zirconium is 1.1 to 1.2:

1.

7. The method for preparing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material according to claim 3, characterized in that: In step 3), the preparation of the zirconium oxide aerogel paper precursor loaded with a half-reacted zirconium silicate precursor comprises the following steps: The zirconia aerogel paper precursor is placed in a hot surface environment of 60-80°C, and the semi-reacted zirconium silicate precursor sol is sprayed on the surface of the zirconia aerogel paper precursor to make it dry and form a film spontaneously under heat; then the zirconia aerogel paper precursor is further dried to obtain a zirconia nanofiber aerogel paper precursor loaded with the semi-reacted zirconium silicate precursor; the spraying amount of the semi-reacted zirconium silicate precursor sol is 25-60 mg / cm 2 The drying temperature is 60-90°C and the drying time is 0.5-2h.

8. The method for preparing the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material according to claim 3, characterized in that: Step 4) specifically includes: placing a zirconium oxide nanofiber aerogel paper precursor loaded with a semi-reacted zirconium silicate precursor in an inert gas atmosphere, first heating from room temperature to 450-500°C at a rate of 0.5-1°C / min, and keeping warm for 30-40 minutes; then heating to 850-900°C at a heating rate of 1-1.5°C / min, keeping warm for 2-3 hours, and then cooling to room temperature; the inert gas is nitrogen or argon.

9. A thermal radiation shielding layer, characterized in that: The thermal radiation shielding layer adopts a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material; the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material includes zirconia aerogel paper, the zirconia aerogel paper is composed of zirconia nanofibers with a diameter of 100 to 400 nm, the surface of the zirconia aerogel paper is loaded with a coating layer of zirconium silicate, the zirconium silicate is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 50 to 200 μm.

10. A multi-layer thermal insulation material, characterized in that: The multilayer thermal insulation material includes a thermal radiation shielding layer, which is made of a carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material; the carbon particle / zirconium silicate / zirconium oxide aerogel paper composite material includes zirconia aerogel paper, which is composed of zirconia nanofibers with a diameter of 100 to 400 nm, and the surface of the zirconia aerogel paper is loaded with a coating layer of zirconium silicate, which is coated with carbon particles with a particle size of 30 to 100 nm, and the thickness of the coating layer is 50 to 200 μm.